Creating inclusive workplaces. (20th May 2022) - Read, Claire
Abstract : How can we build veterinary workplaces that are equally welcoming to all, and in which all are supported to excel? That's the question at the heart of this month's Balance. Here Claire Read speaks to a number of vets from minority ethnic backgrounds to discuss possible answers to this vital question.